2008
DOI: 10.1186/1477-7525-6-16
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch version of the knee injury and osteoarthritis outcome score: A validation study

Abstract: Background: The Knee Injury and Osteoarthritis Outcome Score (KOOS) was constructed in Sweden. This questionnaire has proved to be valid for several orthopedic interventions of the knee. It has been formally translated and validated in several languages, but not yet in Dutch. The purpose of the present study was to evaluate the clinimetric properties of the Dutch version of the KOOS questionnaire in knee patients with various stages of osteoarthritis (OA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
274
5
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(314 citation statements)
references
References 28 publications
22
274
5
6
Order By: Relevance
“…For the selection of activities, an expert group in the field of OA (i.e., physical therapists, a rehabilitation physician, an orthopedic surgeon, a rheumatologist, [human movement] scientists, and patient research partners) used the following sources: the ICF core set for hip and knee OA (18), items in existing self-reported questionnaires (19,20), performance-based tests (21,22), and self-reported activity limitations (by using the Patient-Specific Complaints Questionnaire) (23) collected from 400 patients in the Amsterdam Osteoarthritis (AMS-OA) cohort in an outpatient center for rehabilitation and rheumatology (Reade, Amsterdam, The Netherlands) (24).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…For the selection of activities, an expert group in the field of OA (i.e., physical therapists, a rehabilitation physician, an orthopedic surgeon, a rheumatologist, [human movement] scientists, and patient research partners) used the following sources: the ICF core set for hip and knee OA (18), items in existing self-reported questionnaires (19,20), performance-based tests (21,22), and self-reported activity limitations (by using the Patient-Specific Complaints Questionnaire) (23) collected from 400 patients in the Amsterdam Osteoarthritis (AMS-OA) cohort in an outpatient center for rehabilitation and rheumatology (Reade, Amsterdam, The Netherlands) (24).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…The KOOS consists of 42 items organised into five subscales: pain, other symptoms, function in daily living, function in sports and recreation, and knee-related quality of life. 2 The items are scored on a 5-point Likert scale. For each subscale, the raw score is transformed to a 100-point score.…”
Section: Region-specific Questionnairesmentioning
confidence: 99%
“…Numerous disease-specific or region-specific patientreported questionnaires are used for this purpose. [2][3][4][5][6] However, when one wishes to evaluate and compare outcome amongst different groups of patients or patients with multiple injuries, these questionnaires are not suitable. The Short Musculoskeletal Function Assessment (SMFA) was therefore developed by Swiontkowski et al 7 The SMFA is a patient-reported questionnaire, designed to detect differences in functional status of patients who have a broad range of musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This version has been shown to be valid and reliable for patients with knee OA (de Groot et al, 2008). The KOOS has five distinct sections.…”
Section: Assessment Of Knee Symptoms and Functionmentioning
confidence: 99%